Beyond Tragedy: Differential Commoning in a Manufactured Housing Cooperative. Issue 2 (17th September 2015) - Noterman, Elsa
Abstract: Caught between the dual crises of declining economic opportunity and diminishing public assistance, people on the economic margins resist threats to their livelihoods by opting to share resources. The processes involved in managing these "commons" are often messy and paradoxical amid differing livelihood concerns and subject positions. Unevenness tends to emerge along new and existing lines of power. Rather than reducing such tendencies to a "tragedy" to be eliminated, I argue that grappling with uneven relations offers a more dynamic account of commoning: "differential commoning". This paper takes as its example the residents of a "manufactured housing" community who organized as a cooperative in response to the threat of eviction. Their struggle to collectivize, I suggest, illustrates the need for a more situated conceptualization of commoning, rather than a concept defined within the rigidity of economic rationality or the homogeneity of some imagined community.